2011
DOI: 10.1007/s00420-011-0707-7
|View full text |Cite
|
Sign up to set email alerts
|

A time-stratified case-crossover study of fine particulate matter air pollution and mortality in Guangzhou, China

Abstract: Our findings provided new information for the adverse health effects of PM(2.5) in China, and may have some implications for environmental policy making and standard setting in Guangzhou.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(51 citation statements)
references
References 33 publications
4
45
0
2
Order By: Relevance
“…Reference % increase in mortality Global Review (Atkinson et al, 2014) 1.04 (0.52-1.56) USA (1970)(1971)(1972)(1973)(1974)(1975)(1976)(1977)(1978)(1979)(1980)(1981)(1982)(1983)(1984)(1985)(1986) (Klemm, 2003) (Levy et al, 2012) 1.2 (0.5-1.9) California (1999-2002) (Ostro et al, 2006) 0.6 (0.2-1.0) Spain (2003)(2004)(2005)(2006)(2007)) (Ostro et al, 2011) 1.4 (0.6-2.3) Australia (1996-1999) (Simpson et al, 2005) 0.9 (-0.7-2.5) Beijing (2007Beijing ( -2008) (Chen et al, 2011) 0.53 (0.37-0.69) Guangzhou (2007-2008) (Yang et al, 2012) …”
Section: Place (Study Year)mentioning
confidence: 99%
“…Reference % increase in mortality Global Review (Atkinson et al, 2014) 1.04 (0.52-1.56) USA (1970)(1971)(1972)(1973)(1974)(1975)(1976)(1977)(1978)(1979)(1980)(1981)(1982)(1983)(1984)(1985)(1986) (Klemm, 2003) (Levy et al, 2012) 1.2 (0.5-1.9) California (1999-2002) (Ostro et al, 2006) 0.6 (0.2-1.0) Spain (2003)(2004)(2005)(2006)(2007)) (Ostro et al, 2011) 1.4 (0.6-2.3) Australia (1996-1999) (Simpson et al, 2005) 0.9 (-0.7-2.5) Beijing (2007Beijing ( -2008) (Chen et al, 2011) 0.53 (0.37-0.69) Guangzhou (2007-2008) (Yang et al, 2012) …”
Section: Place (Study Year)mentioning
confidence: 99%
“…Lu et al (2015) found that a 10 μg/m 3 increase in PM 2.5 relates to a 0.63% increase due to CVD mortality. Another study also reported that an increase of 10 μg/m 3 in 2-day moving average concentration of PM 2.5 corresponds to 1.22% increase of CVD mortality (Yang et al, 2011). The latest research (Shah et al, 2013) reviewed that per 10 μg/m 3 increase in PM 2.5 concentration is associated with 2.12% increase of heart failure (HF) hospitalisation or death.…”
Section: Introductionmentioning
confidence: 99%
“…Other research [17] has supported this fact by showing that those under the age of 65 are less likely than their older counterparts to be hospitalized for CVDs during PM2.5 exposure. Women might be more susceptible because of hormones, but research on the interaction between sex and air pollution has not yet proved such a thing [31]. ER visits for respiratory problems occurs more often in the <65 years of age, and sex differences in this case do not differ significantly in the OR.…”
Section: Discussionmentioning
confidence: 98%
“…First, we used outdoor monitoring stations to collect the average daily air pollution levels and other weather variables as our representatives for human exposure to air pollutants. However, other factors -such as the use of air conditioning and the ventilation between indoors and outdoors -might influence how representative our sample truly is, thereby affecting our results and their implications [31]. Second, our study did not include individual behavioral data.…”
Section: Discussionmentioning
confidence: 99%